Efforts to Improve Learning Outcomes Sprint Running Through Reciprocal Teaching Style In SMP VIII State Grade 36 field in the School Year 2018/2019: Efforts to Improve Learning Outcomes Sprint Running Through Reciprocal Teaching Style In SMP VIII State Grade 36 field in the School Year 2018/2019 - Pumareka Tarigan; Ahmad Al Munawar (Journal of Midwifery and Nursing, 2020)
This research is a classroom action research (PTK). This study was conducted in two cycles, with each sikuls consists of planning, action, observation and reflection. Sources of data in this research is the students' test results in the form of penelian portfolio. To analyze the data in this study and to know the results of the study visits of students in the classical completeness, while the method used is a method of a class action. Based on preliminary data obtained by 13 students (37.1%) completed the study while 22 students (62.9%) did not complete the study. The next learning outcomes in the first cycle, totaling 24 students (68.6%) completed the study while 11 students (31.4%) did not complete the study. In the second cycle of 31 students (88, 6%) completed the study while 4 students (11.4%) did not complete the study. This study concludes that through reciprocal teaching styles to improve learning outcomes sprint in class VIII SMP Negeri 36 Medan in academic year 2018/2019.